2018
DOI: 10.2147/ott.s173840
|View full text |Cite
|
Sign up to set email alerts
|

miR-431-5p alters the epithelial-to-mesenchymal transition markers by targeting <em>UROC28</em> in hepatoma cells

Abstract: ObjectiveMicroRNA (miR)-431 plays an essential role in various human cancer types, particularly in the process of invasion. However, the function and mechanism of miR-431-5p in the invasion of hepatocellular carcinoma (HCC) remain undefined.MethodsThe expression levels of miR-431-5p and its potential target protein UROC28 in hepatocellular carcinoma cells and tissues were detected, and the levels of EMT markers in vivo and in vitro were also detected.ResultsMiR-431-5p was downregulated in HCC cell lines and ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 47 publications
(67 reference statements)
4
14
0
Order By: Relevance
“…Upregulation of miR-431-5p prohibits cell proliferation and invasion via ATG3 in colon cancer [19]. Furthermore, miR-431-5p suppresses invasion by targeting UROC28 in hepatocellular carcinoma [18]. Consistent with previous studies, we observed that miR-431-5p overexpression suppresses cell proliferation and G0/G1-to-S phase transition but promoted apoptosis in RA FLSs, suggesting the potential of miR-431-5p in targeting excessively proliferative FLSs in patients with RA.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Upregulation of miR-431-5p prohibits cell proliferation and invasion via ATG3 in colon cancer [19]. Furthermore, miR-431-5p suppresses invasion by targeting UROC28 in hepatocellular carcinoma [18]. Consistent with previous studies, we observed that miR-431-5p overexpression suppresses cell proliferation and G0/G1-to-S phase transition but promoted apoptosis in RA FLSs, suggesting the potential of miR-431-5p in targeting excessively proliferative FLSs in patients with RA.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we have demonstrated that miR-431-5p is downregulated in synovial tissues and FLSs from patients with RA, indicating its potential role in the development of RA. miR-431-5p is associated with the development of various cancers, such as lung cancer, glioblastoma multiforme, colon cancer, and hepatocellular carcinoma [17][18][19]25]. miR-431-5p modulated cell proliferation, apoptosis, autophagy, migration, invasion, and angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upregulation of miR-431-5p prohibits cell proliferation and invasion via ATG3 in colon cancer (18). Furthermore, miR-431-5p suppresses invasion by targeting UROC28 in hepatocellular carcinoma (17). Consistent with previous studies, we observed that miR-431-5p overexpression suppresses cell proliferation and G0/G1-to-S phase transition, but promoted apoptosis in RA FLSs, suggesting the potential of miR-431-5p in targeting excessively proliferative FLSs in patients with RA.…”
Section: Discussionmentioning
confidence: 98%
“…Studies have recently demonstrated that miR-431-5p is dysregulated in various human cancers, such as lung, liver, colon cancer, and squamous cell carcinoma (17)(18)(19)(20). However, the role of miR-431-5p in RA remains to be understood.…”
Section: Introductionmentioning
confidence: 99%